2014
DOI: 10.1590/s0103-84782014000500015
|View full text |Cite
|
Sign up to set email alerts
|

Administração de diferentes concentrações de folhas de Ipomoea asarifolia na ração de camundongos

Abstract: RESUMO Considerando que os principais sinais clínicos observados na intoxicação por

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
3
0
4
Order By: Relevance
“…Apesar de não ser conhecido o principio ativo da I. asarifolia, os sinais clínicos são semelhantes aos de toxinas tremorgênicas, caraterizados por tremores musculares, inicialmente de cabeça e pescoço que posteriormente se generalizam por todo o corpo, culminando com perda de equilíbrio seguido de quedas (Medeiros et al 2003). Também foi determinado em camundongos que o principio ativo ou um metabolito do mesmo tem a capacidade de passar pelo leite intoxicando os filhotes lactentes sem que as mães apresentem sinais (Lopes 2013).…”
Section: Introductionunclassified
“…Apesar de não ser conhecido o principio ativo da I. asarifolia, os sinais clínicos são semelhantes aos de toxinas tremorgênicas, caraterizados por tremores musculares, inicialmente de cabeça e pescoço que posteriormente se generalizam por todo o corpo, culminando com perda de equilíbrio seguido de quedas (Medeiros et al 2003). Também foi determinado em camundongos que o principio ativo ou um metabolito do mesmo tem a capacidade de passar pelo leite intoxicando os filhotes lactentes sem que as mães apresentem sinais (Lopes 2013).…”
Section: Introductionunclassified
“…However, Araújo et al (2008) and Freitas et al (2011) failed to induce the disease in lambs and kids consuming milk from ewes and goats ingesting I. asarifolia. In contrast, preliminary studies in mice show that pups of lactating mothers that were ingesting I. asarifolia become intoxicated and show muscle tremors (Lopes, 2013). This study was conducted to determine in sheep if the tremorgenic toxin of I. asarifolia or a toxic metabolite is eliminated in milk thus causing poisoning in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…With penitren A, the main tremorgenic toxin of Lolium perenne, it was demonstrated that 1-3-day--old mice dosed intraperitoneally were more susceptible than 11-week-old mice (Lu et al 2008). In a previous work, it was observed that dry I. asarifolia mixed 20-30% in the food of 40-day-old mice causes changes in equilibrium and motor coordination, but without tremors (Lopes et al 2014). These results also suggest that newborn mice can be used as an experimental model to study the tremorgenic compound of I. asarifolia.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviour changes without tremors were also observed in weaned of mice ingesting I. asarifolia (Lopes et al 2014). In sheep the poisoning has been observed in nursing lambs that remain confined, without ingesting the plant, while their mothers ingested the plant while grazing without showing signs of disease (Araújo et al 2008, Freitas et al 2011).…”
Section: Introductionmentioning
confidence: 96%